Pengaruh Promosi Dan Harga Terhadap Kepuasan Pelanggan Pada Toko Zae Prima Sibolga - Rika Kiswanti Hutagalung; Dicky Syahputra Lubis (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of promotion and price on customer satisfaction at Toko Zae Prima Sibolga. A quantitative approach was used, with surveys conducted on 40 respondents and analyzed using multiple linear regression. The results indicate that promotion (r = 0.675) and price (r = 0.598) have a positive and significant effect on customer satisfaction, contributing 55% jointly. The study concludes that effective promotion strategies and appropriate pricing increase customer satisfaction.